The Role of HR Training and Work Environment on the Success of ISPO Certification; Study at PT. Agrina Sawit Perdana in West Kalimantan - Kusuma, Armadi Wijaya; Thaib, Danial (Jurnal Bisnis dan Ekonomi, 2025)
Objective : This study aims to examine the influence of human resource (HR) training and the work environment on ISPO certification, as well as assess the role of transparency as a mediating variable at PT. Agrina Sawit Perdana.   Methodology : The research sample consists of 84 employees involved in the ISPO certification process. The study uses a quantitative approach with path analysis and mediation testing techniques to evaluate relationships between variables. The results show that HR training and the work environment have a positive and significant effect on transparency. The work environment also has a direct and significant impact on ISPO certification, while HR training does not have a direct effect on certification. Transparency is proven to be a mediating variable that strengthens the relationship between HR training and the work environment with ISPO certification.   Research results : These findings emphasize the importance of improving training quality and developing a conducive work environment to foster transparency, thereby achieving ISPO certification success more effectively. This research provides managerial implications for PT Agrina Sawit Perdana in managing HR to accelerate and sustain ISPO certification.